2012
DOI: 10.1039/c2cc30814b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of phenothiazines via ligand-free CuI-catalyzed cascade C–S and C–N coupling of aryl ortho-dihalides and ortho-aminobenzenethiols

Abstract: A ligand-free CuI-catalyzed cascade C-S and C-N cross coupling of (hetero)aryl ortho-dihalides and ortho-aminobenzenethiols has been developed, and various phenothiazines were synthesized with excellent regioselectivity. A possible mechanism is proposed for the cascade coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…[5] Zeng et al have identified the copper-catalyzed one-pot synthesis of phenothiazines via the reactions of aryl o-dihalides and o-aminothiphenols via tandem CÀN and CÀS coupling. [6] Wen and Li et al have developed the domino reactions of obromo-arylisothiocyanates and aroylhydrazides as synthetic route to benzo [4,5]thiazolo [2,3-c] [1,2,4]triazoles. [7] Furthermore, the synthesis of 2H-benzo[b] [1,4] thiazin-3(4H)-ones, [8] benzothiophenes, [9] 2-aminobenzothiazoles, [10] benzisothiazol-3(2H)-ones, [11] 2-(arylthio)arylcyanamides, [12] as well as thiazino [2,3,4-hi]indoles [13] have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Zeng et al have identified the copper-catalyzed one-pot synthesis of phenothiazines via the reactions of aryl o-dihalides and o-aminothiphenols via tandem CÀN and CÀS coupling. [6] Wen and Li et al have developed the domino reactions of obromo-arylisothiocyanates and aroylhydrazides as synthetic route to benzo [4,5]thiazolo [2,3-c] [1,2,4]triazoles. [7] Furthermore, the synthesis of 2H-benzo[b] [1,4] thiazin-3(4H)-ones, [8] benzothiophenes, [9] 2-aminobenzothiazoles, [10] benzisothiazol-3(2H)-ones, [11] 2-(arylthio)arylcyanamides, [12] as well as thiazino [2,3,4-hi]indoles [13] have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Due to the great potential of these ubiquitous structural motifs, tireless endeavors have been made towards the synthesis of organochalcogen compounds. [11] In the last decade various reports have been published to construct CÀ S and CÀ Se bonds using photocatalysis, [12] transition metal catalysis, [13] or by activating with different Lewis acids and Brønsted acids. [14] Despite the major progress, these methodologies have been largely restricted from some drawbacks like toxic and pungent reagents, harsh reaction conditions, excess use of oxidants, transition metals, and low scalability.…”
mentioning
confidence: 99%
“…Firstly, we performed the reaction under the similar reaction conditions to the coupling reactions [44]. The expected product was obtained with high yield up to 85 % ( Table 1, entry 1).…”
Section: Resultsmentioning
confidence: 98%
“…As part of our ongoing studies on C-S/C-N cascade coupling reaction (Scheme 1, equation A) [44][45][46][47] and C-X coupling reactions [48][49][50], we revisited tandem C-N/C-S bond formation to synthesize imidazobenzothiazines from 2-mercaptobenzimidazole and 2-iodobenzyl bromide (Scheme 1, equation B) [34], and discovered the transition-metal-free synthesis of imidazobenzothiazines (Scheme 1, equation C).…”
Section: Introductionmentioning
confidence: 99%